Effect of alloy composition on the oxidation‐induced boron depletion in cast Ni‐base superalloy components. Issue 2 (8th May 2016) - Nowak, W. J.; Naumenko, D.; Jałowicka, A.; Young, D. J.; Nischwitz, V.; Quadakkers, W. J.
Abstract : The high temperature air oxidation of the two conventionally cast Ni‐based superalloys Rene 80 containing 92 wt ppm boron and CM 247 containing 110 wt ppm of boron was studied at temperatures between 850 and 1050 °C and times ranging from 1 to 100 h. Analysis by GD‐OES and SEM/WDX/EBSD revealed the surface scale on Rene 80 after exposure at 1050 °C to consist of Cr2 O3 with TiO2 in the outer part and BCrO3 and CrTi2 O5 in the inner part. Internal Al2 O3 precipitates were present below the external scale. After 1 h exposure of CM 247 an inner dense alumina scale formed over eutectic alloy regions containing coarse γ′ precipitates. Over dendritic regions a Cr‐rich oxide scale with BCrO3 ‐precipitates formed initially and aluminum was internally oxidized. After longer oxidation times an alumina sub‐scale grew from the internal precipitates, and oxidation of the initially present depleted alloy zones resulted in formation of outer Ni and Co rich oxides. In both alloys, boron depletion in the bulk alloy occurred due to formation of the mentioned boron rich oxide. The extent of depletion was substantially higher for the chromia forming Rene 80 than for CM 247. In the latter material the boron depletion was suppressed after the formation of the dense, inner alumina scale. Abstract : The high temperature air oxidation of the two conventionally cast Ni‐based superalloys Rene 80 containing 92 wt ppm boron and CM 247 containing 110 wt ppm of boron was studied at temperatures between 850 and 1050 °C and times ranging from 1 to 100 h. In both alloys, boron depletion in the bulk alloy occurred due to formation of boron rich oxide. The extent of depletion was substantially higher for the chromia forming Rene 80.